Factors generating stress in nursing students - Koubri Hayate (EDP Sciences, 2021)
This study aims to explore the perceived stressors among students at the Higher Institute of Nursing professions and Health Techniques (ISPITS) in Rabat, and the coping strategies used. This is a descriptive study, based on the documentary analysis and the interviews, conducted, in 2009, among 500 students from all training courses and 18 administrative and pedagogical managers. Institutional factors (78.8%) are clearly causes that generate students’ stress in relation to personal and environmental factors. Students manage the stress, generated by all factors, adopting emotional, behavioral and cognitive attitudes. The majority of students engage in isolation and loneliness. The interventions of the sections coordinators towards stressed students take the form of listening and psycho-emotional support that they provide to them. Stress among undergraduate students at ISPITS Rabat is a reality. The establishment of a listening team for students, the improvement of learning conditions, good planning and organization of studies, and the dissemination of information and prevention programs to students and teachers are essential measures to deal with student stress. Stress management interventions should be offered to students at the beginning of their training in order to reduce the negative impact of stress and exhaustion on these students.